Cortical Surface Area Rather Than Cortical Thickness Potentially Differentiates Radiation Encephalopathy at Early Stage in Patients With Nasopharyngeal Carcinoma - Zhang, You-ming; Chen, Ming-na; Yi, Xiao-ping; Li, Li; Gao, Jian-ming; Zhang, Jin-lei; Yuan, Xin-ru; Zhang, Na; Liu, Li-zhi; Cai, Pei-qiang; Chen, Bihong T.; Zee, Chishing; et al. (Frontiers in Neuroscience, 2018)
Radiation encephalopathy (RE) is one of the most severe complications in nasopharyngeal carcinoma (NPC) patients after radiotherapy (RT). However, the morphological alteration of early RE is insufficiently investigated. We aimed to investigate the cortical thickness and surface area alterations in NPC patients with or without RE in the follow-up. A total of 168 NPC patients each underwent a single scan and analysis at various times either pre-RT (n = 56) or post-RT (n = 112). We further divided the Post-RT NPC patients into three groups based on the time of the analysis following RT (Post-RT within 6 months, Post-RT 7-12 months) or whether RE signs were detected in the analysis (Post-RT RE proved in follow-up). We confined the vertex-wise analyses of the cortical thickness and surface area to the bilateral temporal lobes. Interestingly, we revealed a gradual increase in the cortical surface area of the temporal lobe with increasing time after RT within the Post-RT RE proved in follow-up group, consistent with the between-group findings, which showed a significant increase in cortical surface area in the Post-RT RE proved in follow-up group relative to the Pre-RT group and the Post-RT within 6 months group. By contrast, such a trend was not observed in the cortical thickness findings. We concluded that the cortical surface area, rather than cortical thickness, may serve as a potential biomarker for early diagnosis of RE.